(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The national system of education of Ukraine urges music teachers to find and implement new forms and methods of classes that will help to form the national identity by engaging primary school pupils to use multimedia technologies. Formation of aesthetic attitudes of younger scholchildren to national folk song by means of multimedia technologies facilitates more efficient aesthetic, intellectual, moral and spiritual development, attracting children to creative research through solving problems of research and creative nature, more fully disclosing their natural inclinations. At present stage of the sstorage of folk song information are reproduced by the computer disks, electronic textbooks , which positively affects on the development of a coherent national cultural identity, its tastes, musical and aesthetic upbringing and acts as a favorable condition and an additional incentive for assimilation of knowledge in both educational processes of the school and in the distance . The introduction of multimedia and distance learning technologies in the classroom practice of music helps to combine didactic function of computer and traditional ways and means of education , enriches and adds to the educational process of an elementary school with new forms of work that promotes more efficient assimilation of musical training material, national folk song,customs and traditions of the Ukrainian people